All-fiber hybrid piezoelectric-enhanced triboelectric nanogenerator for wearable gesture monitoring. (June 2018) - Guo, Yinben; Zhang, Xiao-Sheng; Wang, Ya; Gong, Wi; Zhang, Qinghong; Wang, Hongzhi; Brugger, Juergen
Abstract: With the increasing potential of smart clothing, the demand for generating energy directly in the tissue fibers has prompted for increased research in the field of energy harvesters based on wearable nanogenerators. Current challenges remain in the combination of high output performance, functionalization, and importantly wearing comfort. Herein, an all-fiber hybrid piezoelectric-enhanced triboelectric nanogenerator fabricated by electrospinning silk fibroin and poly(vinylidene fluoride) (PVDF) nanofibers on conductive fabrics is presented. Due to the large specific surface area of nanofibers and the extraordinary ability of silk fibroin to donate electrons in triboelectrification, the hybrid nanogenerator shows outstanding electrical performance, with a power density of 310 µW/cm 2 . This novel all-fiber configuration provides all benefits of ordinary fabrics having flexible appearance and good air permeability, and moreover it can be custom embedded in clothes in any desirable size and shape. Furthermore, the fabricated device allows identifying various types of body motion by a correlation between gesture and corresponding electrical signal. As potential application field, we foresee an autonomous wearable fall alert microsystem for elderly people and persons working in high risk areas. Graphical abstract: An all-fiber hybrid piezoelectric-enhanced triboelectric nanogenerater is fabricated by electrospinning silk fibroin and poly(vinylidene fluoride) nanofibers on conductive fabrics. The device can be applied for gesture detection and timely remote alarm of the unexpected falling-down situation of wearer. The outstanding output performance, functionalization and wearing comfort make it a promising candidate in the area of wearable self-powered real-time health monitoring. fx1 Highlights: An all-fiber hybrid piezoelectric-enhanced triboelectric nanogenerater was proposed. A new self-powered wearable microsystem for falling-down detection and timely remote alarm. Remarkable capability to detect various types of the wearer's body motion and gestures. Outstanding electric output performance with the power density of 3.1 W/m 2 .